The relationship between spiritual intelligence and patience and perceived stress in undergraduate students - Farideh Hosseinsabet; Habil Ataei (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. Background and Objectives: This research investigates the relationship between spiritual intelligence and patience and perceived stress in undergraduate students of faculty of Psychology and Educational Sciences, AllamehTabatabai University. Materials and Methods: The design of this studywas descriptive and correlational .To do so, 150 students were selected using convenience sampling method. They were asked to respond to of the spiritual intelligence (Abdollahzadeh, 2009), patience (HosseinSabet,2007) and Perceived Stress (Cohen, 1983) scales. Data were analyzed using multi-variable regression analysis. Results: The results showed a significant positive relationship between spiritual intelligence and patience, 0/776. Also there was a significant negative relationship between spiritual intelligence and perceived stress, -0/448. Conclusion: This study showed that the higher spiritual intelligence predict higher patience and lower perceived stress. Keywords:spiritual intelligence, patience, perceived stress, students For downloading the full-text of this article please click here.